Effects of electro-mechanical uncouplers, hormonal stimulation and pacing rate on the stability and function of cultured rabbit myocardial slices - Baron, V.; Sommer, S. T.; Fiegle, D. J.; Pfeuffer, A.-K. M.; Peyronnet, R.; Volk, T.; Seidel, T. (Frontiers in Bioengineering and Biotechnology, 2024)
Recent advances have enabled organotypic culture of beating human myocardial slices that are stable for weeks. However, human myocardial samples are rare, exhibit high variability and frequently originate from diseased hearts. Thus, there is a need to adapt long-term slice culture for animal myocardium. When applied to animal cardiac slices, studies in healthy or genetically modified myocardium will be possible. We present the culture of slices from rabbit hearts, which resemble the human heart in microstructure, electrophysiology and excitation-contraction coupling. Left ventricular myocardium from New Zealand White rabbits was cut using a vibratome and cultured in biomimetic chambers for up to 7 days (d). Electro-mechanical uncoupling agents 2,3-butanedione monoxime (BDM) and cytochalasin D (CytoD) were added during initiation of culture and effects on myocyte survival were quantified. We investigated pacing rates (0.5Hz, 1Hz, and 2Hz) and hormonal supplements (cortisol, T3, catecholamines) at physiological plasma concentrations. T3 was buffered using BSA. Contractile force was recorded continuously. Glucose consumption and lactate production were measured. Whole-slice Ca2+ transients and action potentials were recorded. Effects of culture on microstructure were investigated with confocal microscopy and image analysis. Protocols for human myocardial culture resulted in sustained contracture and myocyte death in rabbit slices within 24h, which could be prevented by transient application of a combination of BDM and CytoD. Cortisol stabilized contraction amplitude and kinetics in culture. T3 and catecholaminergic stimulation did not further improve stability. T3 and higher pacing rates increased metabolic rate and lactate production. T3 stabilized the response to β-adrenergic stimulation over 7d. Pacing rates above 1 Hz resulted in progredient decline in contraction force. Image analysis revealed no changes in volume fractions of cardiomyocytes or measures of fibrosis over 7d. Ca2+ transient amplitudes and responsiveness to isoprenaline were comparable after 1d and 7d, while Ca2+ transient duration was prolonged after 7d in culture. A workflow for rabbit myocardial culture has been established, preserving function for up to 7d. This research underscores the importance of glucocorticoid signaling in maintaining tissue function and extending culture duration. Furthermore, BDM and CytoD appear to protect from tissue damage during the initiation phase of tissue culture.